A study on disk index design for large scale de–duplication storage systems. (26th January 2015) - Yang, Tian–Ming; Feng, Dan; Chou, Wen–Kuang; Liu, Jing–Ning
Chunk–based de–duplication storage, which aims to optimise the storage or bandwidth usage by eliminating the duplicate chunks in the inter–file level, has been attended broadly both in academia and industry recently. For a petabyte–scale de–duplication storage system, the metadata storage especially the disk index, which establishes a mapping between the fingerprints and corresponding chunks in the system, can reach terabyte–scale size. In this paper, we propose a disk–resident hash table to implement the disk index, and theoretically study yet extensively experiment the probability of hash table overflow. These studies help us design a space–efficient disk index which not only reduces metadata storage but also improves access performance.